Vaginal Acidity Affects Vaginal Microbiota in Postmenopausal Women - Juminten Saimin; Yenti Purnamasari; Sufiah Asri Mulyawati; Nur Indah Purnamasari; Arimaswati Arimaswati; Ferry Sandra (The Indonesian Biomedical Journal, 2022)
BACKGROUND: The changes in vaginal acidity impact the composition of the vaginal microbiota, either commensal or pathogenic. After menopause, the vaginal tract is more susceptible to infection. Current study was conducted to analyze the effect of vaginal acidity changes on the vaginal microbiota composition in menopausal women.METHODS: A cross-sectional study was conducted on 32 subjects with vulvovaginal atrophy (VVA). Vaginal pH was measured using a strip with colorimetric examination. The detection of Candida sp. was done by using 10% potassium hydroxide. Meanwhile for detection of Trichomonas vaginalis, Gardnerella vaginalis, Lactobacillus iners, and Lactobacillus crispatus, polymerase chain reaction was performed. The data were statistically analyzed.RESULTS: G. vaginalis was the mostly found pathogenic microorganism in current study (40.63%), followed by Candida sp. (25%). Further analysis showed that G. vaginalis were found in L. crispatus positive samples for 9 cases and L. iners positive samples for 9 cases. Candida sp. had an increased risk at vaginal pH ≥6 (OR=8.273), T. vaginalis had a reduced risk at vaginal pH ≥6 (OR=0.765), G. vaginalis had an increased risk at vaginal pH ≥6 (OR=1.440), L. crispatus had an reduced risk at vaginal pH ≥6 (OR=0.077), while L. crispatus had an increased risk at vaginal pH ≥6 (OR=1.111).CONCLUSION: Vaginal acidity alterations in postmenopausal women affect either commensal or pathogenic microorganism composition. A decrease in the number of L. crispatus and an increase in the number of L. iners and pathogenic microorganisms is in line with the increase of pH.KEYWORDS: Lactobacillus, microbiota, menopause, pathogenic microorganisms, vaginal acidity